Utilization of Fly Ash For the Pretreatment Process of Rubber Industry Wastewater Processing Using Hybrid Membrane UF-RO - Meta Mediana; Subriyer Nasir; Hermansyah Hermansyah; Agung Mataram (Program Pascasarjana Universitas Sriwijaya, 2019)
This research was conducted to treat rubber industry wastewater by using fly-ash as an adsorbent and hybrid membrane UF-RO to produce clean water. In this research was analyzed the effect of flow rate of wastewater treatment to remove turbidity, zinc, and iron. The applied flow rate of membrane separation was of 7 L/min and 14 L/min and the operation time was of 90 min respectively. The rejection concentration of turbidity, zinc, and iron decreased with increasing the flow rate at adsorbent fly-ash. Whereas at the hybrid membrane UF-RO, the rejection concentration of turbidity, zinc, and iron increased with increasing the flow rate. The maximum rejection of turbidity was 24.26%, 95%, and 67.89% for adsorbent fly-ash, UF membrane, and RO membrane respectively. The maximum rejection of zinc was 91.67%, 59.70%, and 14.81% for adsorbent fly-ash, UF membrane, and RO membrane respectively. The maximum rejection of iron was 62.24% and 21.62% for adsorbent fly-ash, UF membrane respectively. The pollutants concentration in the permeate was met the quality standards of the Indonesian health department through the decision of the Minister of Health number 907 of 2002 concerning supervision of the quality of drinking water.